2011
DOI: 10.1254/jphs.10277fp
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Inhibition of CYP3A-Mediated Midazolam Metabolism by Anchusan in Rats

Abstract: Abstract. Cytochrome P450 (CYP)-mediated drug interactions caused by Kampo medicine have not been investigated sufficiently. The current study was conducted to reveal the effect of anchusan, a commonly used Kampo formula for gastrointestinal disease, on CYP3A-mediated drug metabolism in rats. The pharmacokinetics of midazolam (MDZ) was investigated after the single or one-week administration of anchusan (500 mg/kg) to evaluate its inhibitory and inducible effect on CYP3A, respectively. MDZ was administrated 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Cárcamo et al [36] showed that exposure of rainbow trouts to pharmacological EMB concentrations altered the transcriptional responses of xenobiotic biotransformation proteins and extrusion transporters. EMB increases CYP3A expression in kidney and intestine samples and it is wellknown that CYP3A enzymes participate strongly in drug interactions [37,38]. Probably, the lipophilic nature of EMB and its non-biotransformation may lead to its accumulation in the plasma and produce changes in many functions including renal, nerve and hepatic functions.…”
Section: Discussionmentioning
confidence: 99%
“…Cárcamo et al [36] showed that exposure of rainbow trouts to pharmacological EMB concentrations altered the transcriptional responses of xenobiotic biotransformation proteins and extrusion transporters. EMB increases CYP3A expression in kidney and intestine samples and it is wellknown that CYP3A enzymes participate strongly in drug interactions [37,38]. Probably, the lipophilic nature of EMB and its non-biotransformation may lead to its accumulation in the plasma and produce changes in many functions including renal, nerve and hepatic functions.…”
Section: Discussionmentioning
confidence: 99%
“…The serum concentrations of MDZ were determined using previously described HPLC methods with slight modifications 22 , 23 , 24 ) . Briefly, 100 µL of each serum sample was diluted with 500 µL of 0.1 N NaOH, and 5 ng of diazepam was added as an internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…After the two treatments with Benifuuki tea, MDZ serum concentrations were measured by an HPLC method previously reported by our laboratory (18,19). Briefly, 100 μl of each serum sample was alkalized and extracted with dichloromethane: pentane (1:1) for 1 min in the presence of diazepam as an internal standard.…”
Section: Methodsmentioning
confidence: 99%